Resistance to Curriculum Changes among Teachers of Madrasah Ibtidaiyah in Indonesia - Wahidmurni Wahidmurni; Samsul Susilawati; Achmad Anwar Abidin (Prodi Manajemen Pendidikan Islam Institut Pesantren KH Chalim Mojokerto, 2024)
The objective of this research is to examine teachers' resistance to curriculum changes occurring in Indonesia, which encompasses aspects of lesson planning, teaching implementation, and learning assessment. This research employed a qualitative approach with a case study design. Data were gathered through interview techniques using focus group discussions involving 20 teachers of Madrasah Ibtidaiyah. Additionally, it encompassed the study of lesson planning documents and learning task outcomes. On top of that, data condensation, data display, and conclusions drawn were also used for data analysis. Furthermore, to ensure the validity of the research findings, data triangulation among various sources was conducted. The research findings showed that teachers' resistance to curriculum changes fell into the moderate category. This was primarily because teachers view curriculum changes as ordinary occurrences. In terms of lesson planning, teachers struggled to identify operational verbs relevant to competency achievement indicators, particularly those related to action verbs from the basic competencies or learning outcomes. Regarding teaching implementation, in addition, teachers still lacked experience in implementing the curriculum recommended, such as Project Based Learning (PjBL) and Problem-Based Learning (PBL). Furthermore, in the aspect of learning evaluation, teachers encountered difficulties in generating questions that prioritized higher-order thinking Skills (HOTS). As a result, the role of the Institute of Teachers' Education (LPTK) and the training institute for teachers' pedagogical and professional competence development needs to be expanded.